Evaluation of the Effective Dose for the Technologists Working in a PET/CT Department in Iraqi Hospitals - kadhum, zeena; Issa, Samar Omran (Iraqi Journal of Physics, 2025)
Nuclear medicine makes considerable use of radioisotopes. Enhancing safe practice and promoting radiation protection measures in the radiology department is greatly aided by the analysis of occupational doses received by medical radiation workers, particularly nuclear medicine staff who deal with radioisotopes. The current study sought to establish the most effective dose of F-FDG18 for PET/CT department personnel. An electronic dosimeter measured the whole-body doses received by technologists during 3 months between March 2024 and May 2024 in two PET/CT departments for eight medical staff, three at Al-Andalus Hospital and five at Al-Kawthar Hospital. In the Al-Andalus Hospital (PET/CT) department, the mean whole-body dose for technologists (1, 2, 3) was (0.19±0.23, 0.055±0.035, and 0.045±0.021) mSv, respectively. At Al-Kawthar H, the average whole-body dosages to technologists (1, 2, 3, 4, and 5) were (0.053 ± 0.005, 0.053 ± 0.005, 0.05 ± 0.01, 0.05 ± 0.01, 0.056 ± 0.015) mSv, respectively. Although the individual doses are under the permissible limits, the increased workload would necessitate greater staff doses. As a result, both facilities must endeavor to examine their operating procedures and lower their radiation dose.